Improvement on Human Resource Planning Capacity of a Hospital in Karangasem Through Workload Indicators of Staffing Need Software Application Training - NMS. Nopiyani; IK. Suarjana; PP. Januraga; P. Muliawan (Research and Community Services Institutes of Udayana University, 2017)
The Workload Indicators of Staffing Need (WISN) software application training aims toimprove the knowledge and skill of Karangasem Regional Public Hospital (RSUD Karangasem) staff in undertaking workload-based human resources planning analysis using WISN software. The training was conducted in 24 September 2016 at RSUD Karangasem. Fifty seven managerial staff of RSUD Karangasem participated in the training. The training consist of WISN software installation, presentation, discussion, and practices on how to use WISN software. The trainees were asked to fill in pretest and posttest questionaires. The test scores were analyzed statistically using paired t-test. There was knowledge improvement of 6,21 after the training with p value < 0.001. All trainees were also able to conduct analysis using WISN software under the guidance of the trainers. The training has been well performed and successfully improved the knowledge and skill of RSUD Karangasem staff in applying WISN method. They stated their willingness to apply WISN method to their institution. However, further technical guidance is required to set up the system for the implementation of WISN method on human resource planning in RSUD Karangasem.